A la recherche du sexe perdu dans la langue - Mora, Luisa (Verbum – Analecta Neolatina, 2023)
Regarding the visibility of women in language, we are currently witnessing a great deal of creativity in Spanish, as well as in many other languages. New words, new neologisms that contravene morphological and syntactic rules are proliferating. All these neologisms are born as a consequence of feminist social movements that claim that language is sexist. The aim of this article is to present the concept of the so-called “linguistic sexism” as well as its evolution in the Spanish language and the inclusive writing associated with it. The difference between sexo and género is dealt with in part 3. Finally (part 4), all different linguistic solutions for inclusive writing in Spanish from a critical point of view are presented.